Advancing Women’s Digital Skills and Economic Empowerment through Girls in Tech Indonesia: A Case Study - Afiani, Isyfi (Salasika, 2018)
The advancing Information and Communication Technology (ICT) has massively supported the economy in the digital era as it disseminates, stores, brings added value and manages information to provide unlimited opportunities for economic development. However, ICT may contribute to discrimination and existing inequalities reinforcement so-called the digital divide. Since all aspects of human interaction with ICT are gendered, this study tackles the digital gender divide issue, that is, the gap between men and women regarding access to, content and use of ICT. Accordingly, in 2016, the gender gap of global internet users was 12% and it grows every year. In response to this condition, a global movement promoting women engagement in ICT has emerged. This study, therefore, depicts the role of Girls in Tech Indonesia community as a chapter of Global Girls in Tech movement in advancing women economic empowerment through ICT by implementing transformational leadership concepts and Longwe’s empowerment framework. In the core of qualitative studies, this study shows that Girls in Tech Indonesia’s leadership performance contributes positively to women empowerment.